RADIASI MEDAN MAGNET FREKUENSI EKSTRIM RENDAH: PENGARUH TERHADAP KONDISI FISIK INTENSITAS KETAN TAPE 500 µT - Hartono, Inggrit Aulya; Hasanah, Fitroh Aysyatun; Zain, Amalia Azizah; Anggraeni, Firdha Kusuma Ayu; Yushardi, Yushardi; Prabandari, Audri Mely (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
The electromagnetic wave spectrum includes extremely low frequency (ELF) magnetic fields, which have a frequency below 300 Hz and are considered non-radiation radiation. This research examines the effect of ELF magnetic fields on the physical condition of white sticky rice tape food, a traditional fermented food in Indonesia. The research is an experimental study that evaluates the physical condition of food ingredients. The research divides the materials into two groups: the control group, which is not exposed to magnetic fields, and the experimental group, which is exposed to magnetic fields with an intensity of 500 µT. The research uses 20 packs of each ingredient, with 10 packs in each group and 100 gr in each pack. The research tests four modules: login page, teacher’s profile update, image upload, and question creation. The research finds that exposure to an ELF magnetic field affects the aroma and texture of food ingredients. Exposure to ELF magnetic fields can speed up the growth of microorganisms. The research observes that the white sticky rice tape in the experimental group has a softer texture than the control group.